Peningkatan Kompetensi Guru untuk Memperkuat Literasi SMA Negeri 5 Purworejo - Umi Faizah; Joko Purwanto; Basuki Basuki; Aris Aryanto; Nurhidayati Nurhidayati; Ari Fajar Isbakhi; Leni Sarofah (Lembaga Pengembangan Kinerja Dosen, 2026)
Strengthening literacy in secondary education is essential in responding to the demands of 21st-century learning. Teachers play a crucial role in integrating literacy into classroom practices; however, their understanding and skills in implementing literacy-based learning are often still limited. This community service program aims to enhance teachers’ competencies in developing literacy-based instruction at State Senior High School 5 Purworejo through a participatory and sustainable training and mentoring approach. The program involved 30 teachers and was conducted in three stages: preparation and planning, implementation, and mentoring and evaluation. The results show a significant improvement in teachers’ understanding of literacy, with the average score increasing from 62.4 to 84.7. A total of 87% of teachers were able to design literacy-based lesson plans effectively, while 73% successfully implemented them in classroom practice. Positive impacts were also observed among students, who became more active in discussions and more confident in expressing their ideas. Qualitatively, the program revealed a shift in teachers’ perspectives, where literacy is no longer seen as an additional activity but as an integral part of meaningful learning that fosters critical and reflective thinking. Overall, this program not only improved teachers’ technical competencies but also strengthened their professional awareness in creating more meaningful learning experiences. The mentoring process played a key role in supporting this transformation by providing a reflective and supportive space for continuous learning and growth.